Quantification and health impact assessment of polycyclic aromatic hydrocarbons (PAHs) emissions from crop residue combustion. Issue 3 (March 2022) - Fakinle, Bamidele Sunday; Odekanle, Ebenezer Leke; Ike-Ojukwu, Chika; Sonibare, Omowonuola Olubukola; Falowo, Olayomi Abiodun; Olubiyo, Folawemi Winner; Oke, Daniel Olawale; Aremu, Charity O.
Abstract: Emission of Polycyclic Aromatic Hydrocarbon compounds from combustion of crop residue was investigated. Crop residues comprising maize cobs, maize husks, rice husks and bean chaff were burnt in a furnace at a temperature of 400 °C and the emissions from the combustion process were characterized using standard methods. Health risk through inhalation was assessed using toxic equivalent factors and excess lifetime cancer risk. The results showed the detection of 16 PAH compound which included: Benzo[ghi]perylene, Naphthalene, Acenaphthene, Anthracene, Phenanthrene, Fluorene, Fluoranthene, Acenaphthylene, Pyrene, Benzo[a]anthracene, Dibenzo[a, h]anthracene, Benzo[b]fluoranthene, Chrysene, Benzo[a]pyrene, Indene[1, 2, 3-cd]pyrene and Benzo[k]fluoranthene. Benzo[b]fluoranthene had highest mean concentration of 1.30 μg/mg while Dibenzo[a, h]anthracene had the lowest mean concentration of 0.01 μg/mg. It was also revealed that the toxicity of PAHs was due to the presence of Benzo[b]fluoranthene for all the samples except for sample 4 for which the main contribution to toxicity was emission from benzo(a)pyrene, while the cancer risk assessment estimated to be 1.2 × 10 −1 was far above the acceptable carcinogenic risk limit of 1 × 10 −6 . This study concluded that, more efforts are needed to reduce emission of PAHs from the combustion of crop residues into the ambient air otherwise, human health could be under threat especially if exposed for a long period. Abstract : Aromatic hydrocarbon; Combustion; Crop residue; PAHs; Pollutants.